2021
DOI: 10.4317/jced.57827
|View full text |Cite
|
Sign up to set email alerts
|

Dental pain associated with untreated dental caries and sociodemographic factors in 5-year-old children

Abstract: Background The aim of this study was to assess the prevalence of dental pain and to examine its association with untreated dental caries in 5-year-old children. Material and Methods This was a cross-sectional study of 261 5-year-old children in Northeast Brazil. Parents answered questions about their socioeconomic conditions and their children’s toothache. Trained dentists assessed dental caries using the decayed, missing and filled teeth (dmf-t) index. Binary logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…This suggests that both dental pain and caries may constitute common problems among Mexican schoolchildren, as untreated caries are associated with dental pain [2,20,35,38]. The present study found a correlation of dental pain with dental caries, a finding similar to the results described in the literature [37][38][39]. The presence of severe caries is often associated with dentin exposure and, in the most severe cases, with pulpal inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that both dental pain and caries may constitute common problems among Mexican schoolchildren, as untreated caries are associated with dental pain [2,20,35,38]. The present study found a correlation of dental pain with dental caries, a finding similar to the results described in the literature [37][38][39]. The presence of severe caries is often associated with dentin exposure and, in the most severe cases, with pulpal inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, parental reports of children's dental pain experience might not always accurately reflect the child's perception. However, they play an important role in planning dental treatment, as the experience of their child's dental pain is often associated with the status of caries [1,7,8]. Therefore, parental reports of children's dental pain experience are a valid tool that assists in dental diagnosis, guides treatment decisions, and determines the choice of management techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Within Brazilian preschool-age children, its prevalence seems to range from 9.4 to 21.1 percent, and it is often associated with dental caries [1,7]. In this context, the experience of dental pain has been considered the most common symptom or consequence of the presence of untreated dental caries [8].…”
Section: Introductionmentioning
confidence: 99%
“…Bakar et al found that the prevalence of toothache among Indonesian children was 15.55% (18). According to Paredes et al, the prevalence of dental pain in 5-year-old children in Northeast Brazil was 28.7% (19).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the prevalence of toothache have identified some factors associated with toothache prevalence in 12-year-old children. These factors include dental caries, socioeconomic status, and parental awareness of children's health conditions (16)(17)(18)(19)23). Moreover, people who lived in deprived areas and had limited access to dental services appeared to have more untreated caries and experience more pain (15,(24)(25)(26), and regular dental visits were associated with a reduced prevalence of toothache (27).…”
Section: Introductionmentioning
confidence: 99%